Family affluence and cultural capital as indicators of social inequalities in adolescent's eating behaviours: a population-based survey - Fismen Anne-Siri; Samdal Oddrun; Torsheim Torbjørn (BMC, 2012)
Abstract Background Dietary inequality, via socio-economic inequality, may involve several mechanisms. Different aspects of adolescents' socio-economic circumstances should therefore be considered in order to make effective interventions to promote healthy eating in the young population. Indicators designed to tap socio-economic status among adolescents in particular will facilitate a better understanding of the concept of socio-economic status and how it influences health behaviour among young people. The purpose of this study was to evaluate if material capital and cultural capital individually and independently contribute to the prediction of eating habits in the Norwegian adolescent population. Methods The analysis is based on survey data from the Health Behaviour in School-Aged Children study. The Family Affluence Scale (number of cars, holidays, PC and bedrooms) and number of books in the household were used as indicators of socio-economic status, respectively measuring material capital and cultural capital. Their influence on adolescent's consumption of fruit, vegetables, sweets, soft drinks, and consumption of breakfast and dinner was evaluated. Pearson's correlation, logistic regression and ridit transformation analysis were used to analyse the data. Results Higher family affluence was shown to predict consumption of more fruit (OR 1.52) and vegetables (OR 1.39) and consumption of breakfast (OR 1.61) and dinner (1.35). Cultural capital was significantly associated to consumption of fruit (OR 1.85), vegetables (OR 2.38) sweets (OR .45), sugary soft drinks (OR .26), breakfast (OR 2.13) and dinner (OR 1.54). Cultural capital was the strongest predictor to healthy eating among adolescents in Norway. Conclusions Material capital and cultural capital individually and independently contributed to the prediction of healthy eating patterns among adolescents in Norway. Cultural capital is an understudied dimension of the socio-economic status concept and the influence on health behaviour needs to be explored in future studies. Initiatives to promote healthy eating should focus on education, habits and consciousness of a healthy diet, but also at reducing the high cost of fruit and vegetables. There is further a need for developing appropriate indicators for adolescent socio-economic status.